Evaluation of physicochemical properties of Trigona sp. stingless bee honey from various districts of Johor - Harisun Ya’akob,; Nur Fatiha Norhisham,; Muna Mohamed,; Norasiah Sadek,; Susi Endrini, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Johor as one of the states of Malaysia is a good geographic location for meliponiculture activity. In this study, ten samples of stingless bee honey from each regions of Johor and one sample obtained from Institute Bioproduct Development, Universiti Teknologi Malaysia, Skudai were analyzed for the physicochemical properties of stingless bee honey. The physicochemical analyses were including moisture, total soluble solids, ash, pH, free acidity, conductivity, hydroxymethylfurfural (HMF) content, protein, carbohydrate, fat, dietary fibre, total phenolic content (TPC), total flavonoid content (TFC), and DPPH radical scavenging activity. Trigona sp. sample from Kluang have the highest value of phenolic content (778.23 ± 2.011 mg GAE/100 g) while Trigona sp. sample from Mersing have the highest value of flavonoid content (194.98 ± 0.350 mg RE/100 g). Among eleven samples tested for radical scavenging activity, Trigona sp. sample from Kota Tinggi have the highest scavenging activity (23.37 ± 0.36 mg/ml), but the value of HMF content exceeded the limit of Malaysian standard for stingless bee honey. All parameters were significantly different (p < 0.01) except for ash. This study showed a strong correlation between moisture and acidity (r = 0.601). However, low correlation was obtained between TPC and TFC with DPPH radical scavenging activity (r = -0.235, 0.011). The data obtained from this study could help for a better subsequent of Malaysian stingless bee honey industry.